ANALISIS PENGGUNAAN BAHASA GAUL NETIZEN TIKTOK DALAM KASUS INARA RUSLI - Muhammad Fahrul Roji Nasution; R Panji Hermoyo (STKIP Subang, 2026)
This study aims to explore slang in the TikTok comment column on the Inara Rusli affair case through a philosophy of language perspective in order to explore the correlation with the mastery of Indonesian language users' understanding. This research combines content analysis and qualitative descriptive methods, examining forms of linguistic innovation in the form of abbreviations, acronyms, loanwords, modifications, and puns currently developing in cyberspace, particularly digital. This research is grounded in the ideas of Ludwing Wittgenstein, J.L. Austin, and John Searle. These include the theory of meaning is use and speech act theory, which discusses how language meaning is determined by its use in social practice, as well as several secondary sources, including articles and books. The results of this study reveal that the transformation of slang on TikTok is not only a typical expression of the spontaneity of the younger generation but also represents a new perspective on thinking and communicating in the digital age. Philosophically, this phenomenon also reflects that the breadth of vocabulary reflects the breadth of human thought horizons, so that meaning is not only the result of linguistic structures but also a social construction that exists within user communities. Therefore, reflective awareness is needed to balance digital language creativity with formal vocabulary mastery so that communication in the digital age is meaningful and responsible.